PELATIHAN PENGOLAHAN DATA STATISTIK DENGAN MENGGUNAKAN APLIKASI PROGRAM SPSS BAGI MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TIMOR DEMI MENINGKATKAN KUALITASKARYA ILMIAH MAHASISA - Emilia Khristina Kiha; Sirilius Nafanu (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The purpose of service is to provide training on the basics of statistical theory and various types of research and how to determine the right analysis tool according to research needs and provide training in data processing from tabulation, analysis to interpretation of processed statistical data using the SPSS program application. The service location is at the Faculty of Economics and Business, University of Timor. Participants who are the object of training in this service are students of the Faculty of Economics and Business, University of Timor both from the Development Economics and Management Study Program. However, the focus of the training participants is limited by a number of requirements which include: Active and temporary students programming or having passed the Research Methodology Course, are in the sixth semester and are willing to attend training until completion. The training activities for processing statistical data using SPSS for students of the Faculty of Economics and Business (FEB) to improve the quality of scientific work of FEB Unimor students were held for three stages / day.